The influence of incorporation of Mn on the pitting corrosion performance of CrFeCoNi High Entropy Alloy at different temperatures. (15th December 2019) - Torbati-Sarraf, H.; Shabani, Mitra; Jablonski, Paul D.; Pataky, Garrett J.; Poursaee, A.
Abstract: The electrochemical behavior and susceptibility to pitting corrosion of CrFeCoNi and CrMnFeCoNi high entropy alloys were studied in a 0.1 M NaCl solution at temperatures ranging from 25 to 75 °C. Electrochemical measurements revealed that CrMnFeCoNi is more susceptible to oxide film breakdown and localized corrosion compared to CrFeCoNi. Post corrosion microscopic observations showed severe pitting corrosion for CrMnFeCoNi in higher temperatures compared to CrFeCoNi. Based on in-depth XPS profile measurements on the remaining oxide films, this behavior was attributed to the depletion of Cr in the oxide film and detrimental presence of Mn in the matrix solid solution of CrMnFeCoNi. Graphical abstract: Unlabelled Image Highlights: Incorporation of Mn into CrFeCoNi impairs corrosion resistance of the solid solution. The CPT for CrMnFeCoNi was much lower than that of CrFeCoNi. Pits on the surface of the CrMnFeCoNi were larger and deeper than those on CrFeCoNi. Alternative EIS data representation provides accurate information about corrosion.